Meaning in life among Chinese undergraduate students in the post-epidemic period: A qualitative interview study - Ge, Ying; Lu, Cun Yang; Shuai, Mei Qiong; Wenger, Jay L.; Peng, Chun Hua; Wang, Hong (Frontiers in Psychiatry, 2022)
Background COVID-19 epidemic has lasted for nearly 3 years, and revolutionized social life. In the study, in-depth interviews were conducted with Chinese undergraduate students to explore their understanding and experience of meaning in life. Meaning of life is interpreted from four aspects: life goals, life value, life enthusiasm, and life freedom. These four aspects are independent yet interrelated. Based on the free grasp of life, individuals explore and pursue the true meaning of life goals, acquire life value in evaluating the completion of life goals, and subsequently experience enthusiasm for life. Life enthusiasm and the perception of life value can help individuals to further understand and possess their meaning of life. Materials and methods The present study adopts the qualitative method to understand the experience of meaning in life among Chinese undergraduate students. Semi-structured interviews were conducted, and six people participated the study. The Grounded Theory was adopted to analyze the qualitative data. Results (1) Chinese undergraduates had clear life goals and obtained a certain sense of achievement and satisfaction when striving for these goals. (2) The life value of Chinese undergraduates was mainly to their families, but there was also a willingness to make due contributions to the country and society. (3) Chinese undergraduates’ feelings about life were polarized, but they all expressed the view of “living in the moment and cherishing the present.” (4) Chinese undergraduate students see life freedom as freedom of choice and generally believed that COVID-19 did not restrict their lives very much. (5) Chinese undergraduate students gained a deeper understanding of meaning in life after this major public health emergency.